2011
DOI: 10.1242/dev.066480
|View full text |Cite
|
Sign up to set email alerts
|

Specific expression of a TRIM-containing factor in ectoderm cells affects the skeletal morphogenetic program of the sea urchin embryo

Abstract: SUMMARYIn the indirect developing sea urchin embryo, the primary mesenchyme cells (PMCs) acquire most of the positional and temporal information from the overlying ectoderm for skeletal initiation and growth. In this study, we characterize the function of the novel gene strim1, which encodes a tripartite motif-containing (TRIM) protein, that adds to the list of genes constituting the epithelial-mesenchymal signaling network. We report that strim1 is expressed in ectoderm regions adjacent to the bilateral clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…This provides evidence of cross-talk between these two pathways, which function synergistically in other systems (Tomanek et al, 2010). Cavalieri et al (Cavalieri et al, 2011) showed that the tripartite motif-containing protein STRIM1 regulates the expression of fgfa in the ectoderm, but not in PMCs, highlighting the separate control of fgfa expression in these two tissues. STRIM1 also regulates otp in the ectoderm whereas VEGF3 and FGFA do not, suggesting that multiple pathways regulate gene expression in the ectoderm overlying the VLCs.…”
Section: Research Article Growth Factors In Cell Guidancementioning
confidence: 93%
See 1 more Smart Citation
“…This provides evidence of cross-talk between these two pathways, which function synergistically in other systems (Tomanek et al, 2010). Cavalieri et al (Cavalieri et al, 2011) showed that the tripartite motif-containing protein STRIM1 regulates the expression of fgfa in the ectoderm, but not in PMCs, highlighting the separate control of fgfa expression in these two tissues. STRIM1 also regulates otp in the ectoderm whereas VEGF3 and FGFA do not, suggesting that multiple pathways regulate gene expression in the ectoderm overlying the VLCs.…”
Section: Research Article Growth Factors In Cell Guidancementioning
confidence: 93%
“…We also examined two other genes expressed in the ectoderm that have been shown to play a role in regulating skeletogenesis: otp (Di Bernardo et al, 1999;Cavalieri et al, 2003) and pax2/5/8 (Cavalieri et al, 2011). Lv-pax2/5/8 expression was slightly downregulated in Lv-vegf3 morphants (supplementary material Fig.…”
Section: Research Articlementioning
confidence: 99%
“…2J). Thus, the candidate LOF effects are distinct from those produced by knockdown of VEGF/R, Wnt5a, Otp, Pax2/5/8 or FGF, because each of the latter LOFs blocks biomineralization, resulting in larvae that lack skeletons entirely (Di Bernardo et al, 1999;Cavalieri et al, 2003;Duloquin et al, 2007;Rottinger et al, 2008;Cavalieri et al, 2011;AdomakoAnkomah and Ettensohn, 2013;McIntyre et al, 2013). Furthermore, each candidate LOF resulted in perturbed PMC organization at the LG stage (Fig.…”
Section: Sb and Nickel Have Opposite Effects On Ectodermal Specificatmentioning
confidence: 99%
“…These include the tripartite motif-containing protein Strim1, the transcription factors Pax2/5/8 and Otp, the signaling ligands FGF, Wnt5a, VEGF and the TGF-β ligand Univin. These genes are expressed in the ectoderm directly adjacent to sites of active biomineralization and with the exception of Univin, which is specifically required for patterning of the secondary skeletal elements (Piacentino et al, 2015), their loss of function (LOF) blocks skeletogenesis, indicating a role in regulating biomineralization (Di Bernardo et al, 1999;Cavalieri et al, 2003;Duloquin et al, 2007;Rottinger et al, 2008;Cavalieri et al, 2011;Adomako-Ankomah and Ettensohn, 2013). Gene products that specifically regulate primary PMC positioning but not biomineralization, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the intervening time, subpopulations of primary mesenchyme cells migrate within the blastocoel cavity guided by signals emitted by these regions, settle into two ventrolateral aggregates adjacent to the ectoderm thickenings, and eventually mineralize two skeletal primordia [19][20][21]. At the end of gastrulation, the opening of the larval mouth occurs by bending of the archenteron towards the ventral ectoderm and subsequent fusion of the two epithelia.…”
Section: Introductionmentioning
confidence: 99%